2005
DOI: 10.1007/s00122-005-0049-5
|View full text |Cite
|
Sign up to set email alerts
|

Paternity analysis using microsatellite markers to identify pollen donors in an olive grove

Abstract: Olive (Olea europaea L.) is a wind-pollinated, allogamous species that is generally not considered to be self-compatible. In addition, cross-incompatibilities exist between cultivars that can result in low fruit set if compatible pollinisers are not planted nearby. In this study, microsatellite markers were used to identify 17 genotypes that were potential pollen donors in a commercial olive orchard. DNA typing with the same primers was also applied to 800 olive embryos collected from five cultivars in the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
64
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 29 publications
17
64
2
2
Order By: Relevance
“…Under the environmental conditions of this study, 'Frantoio' was self-incompatible (IPI0 0.00), which agrees with the findings of Wu et al (2002) and Mookerjee et al (2005), while it was previously recorded as self-compatible in Australia (Sharma et al 1976) and in some other countries (Fontanazza & Baldoni 1990;Fabbri et al 2004). 'Frantoio' (as a host) was also crossincompatible with 'Barnea' and 'Koroneiki' but partially compatible with 'Mission'.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Under the environmental conditions of this study, 'Frantoio' was self-incompatible (IPI0 0.00), which agrees with the findings of Wu et al (2002) and Mookerjee et al (2005), while it was previously recorded as self-compatible in Australia (Sharma et al 1976) and in some other countries (Fontanazza & Baldoni 1990;Fabbri et al 2004). 'Frantoio' (as a host) was also crossincompatible with 'Barnea' and 'Koroneiki' but partially compatible with 'Mission'.…”
Section: Discussionsupporting
confidence: 90%
“…The same result was also obtained by Mookerjee et al (2005) in South Australia. Results from the present study showed that 'Koroneiki' (as a host) was incompatible with 'Barnea' and partially compatible with 'Frantoio' and 'Mission' while Mookerjee et al (2005) found incompatibility between 'Koroneiki' (as a host) and 'Frantoio'. They also observed that 'Mission' was the best pollen donor for 'Koroneiki'.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In Olea europaea, these markers have been used for different applications such as cultivar discrimination (Sarri et al 2006;Fendri et al 2010), study of relationships between wild and cultivated olive tree (Belaj et al 2007), construction of association maps (De la Rosa et al 2003), paternity analysis (Mookerjee et al 2005) and identification of olive oil varietal composition (Alba et al 2009;Ayed et al 2009;Rabiei et al 2010). A list of recommended SSR markers and protocols for olive genotyping has been provided with the aim to develop a robust method to track the origin of olive cultivars (Doveri et al 2008;Baldoni et al 2009 Table 4.…”
Section: Simple Sequence Repeats (Ssrs)mentioning
confidence: 99%
“…With regard the paternity analysis, SSRs are the most suitable to trace the genetic contribution of alleles from the parents to the offspring, being co-dominant and highly polymorphic markers (Mookerjee et al 2005). The effectiveness of SSRs in the identification of paternity contribution to progeny obtained from olive breeding programs has been demonstrated by several authors (De la Rosa et al 2004;Diaz et al 2007).…”
Section: Paternity Analysismentioning
confidence: 99%